(3LQGFe ZSd GdGehGd ai GdJTQjYjf GdGeGQGJi hGdeUQj (B/ s - (3MeO eMeO Sja GdYdjdis; (3YeQ eMeO eMeO SGd`es; (3LGeYI GdbGgQIs (3cdjI GdMbhbs ((3GdbGgQI (B: s (3cdjI GdMbhb(B-(3LGeYI GdbGgQI,s, 2007)
(3jYO ZS`d GdGehGd ef GdXhGgQ GdGLQGejI GdJi GcJTaJ MOjKG ; aGdZSd ai PGJg cGf jQJcH ef bHd (B: (3hPdc HeMGhdI JWgjQ Gh ZSd GdGehGd PGJ GdeUOQ ZjQ GdeTQhY MJi JHOh ai eUOQ eTQhYhfXQG dNWhQI gPg GdXGgQI Ydi GdeSJhjGJ GdGNdGbjI (B: (3hGdGLJeGYjI (B: (3hGdGbJUGOjI abO GJLgJ GdJTQjYGJ GdeNJdaI Gdi ecGaMJgG ; abO GefJ Gf GdGMcGe GdJbdjOjI ai bGfhf GdYbhHGJ ZjQ cGajI dgPg GdehGLgI GP KHJ YLR GdeSGgeI GdLfGFjI GdJHYjI (B: (3hKHJ cPdc YLR GddLhA Gdi LQjeI GNaGA GdGTjGA GdeSQhbI Gh GdeJMUdI ef LfGjI Gh LfMI hef Gge GdJTQjYGJ GdJi hGLgJ gPg GdXGgQI hhVYJ dgG GdjGJ NGUI ddecGaMI GdJTQjY GdaQfSi hGdeUQi hGdGeGQGJjhbO GJabJ gPg GdJTQjYGJ GdKdGKI ai adSaI GdecGaMI GdehVhYjI hGdGLQGFjI (B: (3h Gf GNJdahG ai HYV GdJaUjdGJs
(3GWQhMI (B((3eGLSJjQ(B) - (3LGeYI GdbGgQI (B- (3cdjI GdMbhb (B- (3bSe GdbGfhf GdLfGFi, (B2007s
(3jTJed Ydj EQLGYGJ HdjhLQGajI(B: (3UaMI (B188-193s
(3GdfU HGdYQHjI hGdedNU HGddZI GdaQfSjI hGdYQHjI(B.s
Keywords: (3GdbGfhf GdLfGFjs; (3GdJTQjY GdGeGQGJjs; (3GdJTQjY GdeUQjs; (3ZSd GdGehGds; (3LQGFe ZSd GdCehGd ai GdGJaGbjGJ GdOhdjIs; (3GdQcf GdeGOi ai LQjeI ZSd GdCehGds; (3GdQcf GdeYfhi ai LQjeI ZSd GdCehGds; (3YbhHI LQjeI ZSd GdCehGds; (3GdCMcGe GdELQGFjI dLQjeI ZSd GdCehGds; (3JbGOe GdOYhi GdLfGFjI ai LQjeI ZSd GdCehGds; (3GdJYGhf GdOhdi ai ELQGAGJ ehGLgI ZSd GdCehGds; (3QSGFd LGeYjIs -- (3LGeYI GdbGgQIs -- (3GdbGfhf GdLfGFjs